Characterizing the inhibitory action of zinc oxide nanoparticles on allergic-type mast cell activation. Issue 2 (August 2015) - Feltis, B.N.; Elbaz, A.; Wright, P.F.A.; Mackay, G.A.; Turney, T.W.; Lopata, A.L.
Highlights: Mast cell degranulation can be inhibited by ZnO nanoparticles. This inhibition was nanoparticle size and dispersion dependent. ZnO nanoparticles had higher cytotoxicity to cancerous cells (RBL-2H3) compared to primary mast cells (BMMCs). TiO2 nanoparticles slightly increased mast cell degranulation. These nanoscale enhancements in ZnO bioactivity of may lead to the development of novel anti-allergic therapeutics. Abstract: The development of nanoparticles (NPs) for commercial products is undergoing a dramatic expansion. Many sunscreens and cosmetics now use zinc oxide (ZnO) or titania (TiO2 ) NPs, which are effective ultraviolet (UV) filters. Zinc oxide topical creams are also used in mild anti-inflammatory treatments. In this study we evaluated the effect of size and dispersion state of ZnO and TiO2 NPs, compared to "bulk" ZnO, on mast cell degranulation and viability. ZnO and TiO2 NPs were characterized using dynamic light scattering and disc centrifugation. Rat basophilic leukaemia (RBL-2H3) cells and primary mouse bone marrow-derived mast cells (BMMCs) were exposed to ZnO and TiO2 NPs of different sizes (25–200 nm) and surface coatings at concentrations from 1 to 200 μg/mL. The effect of NPs on immunoglobulin E (IgE)-dependent mast cell degranulation was assessed by measuring release of both β-hexosaminidase and histamine via colorimetric and ELISA assays. The intracellular level of Zn 2+ and Ca 2+ ions were measured using zinquin ethyl ester and Fluo-4 AM fluorescence probes, respectively. Cellular viability was determined using the soluble tetrazolium-based MTS colorimetric assay. Exposure of RBL-2H3 and primary mouse BMMC to ZnO NPs markedly inhibited both histamine and β-hexosaminidase release. This effect was both particle size and dispersion dependent. In contrast, TiO2 NPs did not inhibit the allergic response. These effects were independent of cytotoxicity, which was observed only at high concentrations of ZnO NPs, and was not observed for TiO2 NPs. The inhibitory effects of ZnO NPs on mast cells were inversely proportional to particle size and dispersion status, and thus these NPs may have greater potential than "bulk" zinc in the inhibition of allergic responses.